Effect of Uncertainty on Adherence and Quality of Life in Breast Cancer Survivors: A Systematic Review - Harianto, Susilo; Nursalam, Nursalam; Sulpat, Emuliana; Mardhika, Amellia (International Journal of Psychosocial Rehabilitation, 2020)
Quality of life takes precedence in the terminal stages of disease, such as breast cancer survivor, when a cure is considered impossible and all alternative methods to prevent disease progression have been exhausted. Given the distress associated with a cancer diagnosis, the treatments and their side effects, as well as the uncertainty of outcomes, it has been suggested that psychosocial factors ought to be considered as an important aspect of breast cancer treatment. The purpose of this research was to assess the effect of uncertainty on adherence and quality of life in breast cancer survivors. A systematic review of the literature concerning uncertainty, adherence and quality of life for patients with breast cancer was conducted by searching PubMed (including Medline), Web of Science, CINAHL Plus, Embase, Breast Cancer Research, The Cochrane Library and Google Scholar Database for articles featuring the terms “uncertainty”, “adherence”, “quality of life”, “cancer” and “breast cancer”. Eligible studies were those whose title or abstract specifically indicated the inclusion of breast cancer patients. There were no restrictions regarding participants’ age, number of participants, or disease stage and the studies were analyzed using prisma. The results of the studies confirmed that the effects of uncertainty were significant, alluding to the possibility to enhance adherence and quality of life in breast cancer survivors. Distress from prognostic uncertainty are associated with adherence and quality of life in breast cancer patients. The findings of this review encourage efforts to further research to enhance quality of care and better quality of life in breast cancer survivors.